Answers

2015-07-13T23:16:51+08:00
3x-[5x-(2x-8)]
= 3x-(5x-2x+8)
= 3x-(3x+8)
= 3x-3x-8
= -8
(^_^)
1 5 1
2015-07-14T12:21:53+08:00
Simplifying  3x + -1[5x + -1(2x + -8)]
Reorder the terms: 3x + -1[8 + 5x + -2x]
Combine like terms:  5x + -2x = 3x
                                 3x + -1[8 + 3x]
                                 3x + [8 * -1 + 3x * -1]
                                 3x + [-8 + -3x]
Reorder the terms: -8 + 3x + -3x
Combine like terms: 3x + -3x = 0
                                    -8 + 0 = -8
0